The Effectiveness of Pictionary Game on Vocabulary Mastery on The Eight Grade Students of SMPU Al-Anwari Banyuwangi - Dita Wiji Lestari; Abdul Halim; Arin Inayah (LUNAR, 2019)
This research was aimed to get the empirical evidence of the effectiveness of Pictionary Game on students’ vocabulary retention. The method that was used was a quantitative method. The design of this research was quasi-experimental. This research was conducted in SMPU AL-Anwari Banyuwangi. The number of the sample of the research was 50 students of eighth grade. The instrument of this research was tests. The tests were divided into two, there were pre-test and post test The purpose of this research was to measure there is an effectiveness of Pictionary game on the vocabulary mastery of the eighth grade students‟ of SMPU Al-Anwari Banyuwangi in the 2017/2018 academic year. The area of this research was SMPU Al-Anwari Banyuwangi. It was chosen purposively because they have never been taught by using “Pictionary Game” at this school. Another reason was that the permission to conduct this research in this school from the headmaster has already accepted.